No increase in total red blood cell volume during three weeks of training at an altitude of 1,800 m - Friedman, B.; Jost, J.; Rating, T.; Mairbauri, H.; Bartsch, P. (Medicine & Science in Sports & Exercise, 1996)
The effect of iron supplementation on total red blood cell volume (RBV) in non-iron deficient athletes (German national boxing team) during a three week camp focusing on endurance training at 1,800 m was assessed. The endurance training caused increased destruction/loss of erythrocytes. It was concluded that iron supplementation did not enhance erythropoiesis. The lack of an increase of RBV might be explained by a small erythropoietic stimulus caused by the brief exposure to moderate altitude. Implication: It is often suggested that endurance athletes take iron supplements when training at altitude. This study found that to be unnecessary, which is contrary to other published opinions. Until this matter is clearly resolved, it is recommended that moderate iron supplements be taken as a conservative hedge for individuals who might be very susceptible to RBV loss at altitude.